Focussed ion beam sectioning for the 3D characterisation of cracking in oxide scales formed on commercial ZIRLO (TM) alloys during corrosion in high temperature pressurised water - Ni, N; Lozano-Perez, S; Sykes, J; Smith, G; Grovenor, C (2011)
Using FIB sectioning and reconstruction techniques we have performed a quantitative analysis on the microstructure of cracks and the topography of the metal-oxide interface in oxides formed on ZIRLO™ alloys in high-temperature water. The most significant observation is the continuous production of cracks both before and after the transition in kinetics, not a sudden burst of crack nucleation at transition as assumed in the literature. By concluding that cracks are not generated as a result of the transition and are not the primary cause, we suggest that a process by which cracks within the scale become connected to the oxidising environment through interconnected nanoporosity may be critical in controlling the overall rate of oxidation. © 2011 Elsevier Ltd.